The Pharmacy in the New Era of Artificial Intelligence : Pharmacy and Artificial Intelligence - Ortega Urbano, Monica Doralis (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
Artificial intelligence has become a key piece of human knowledge and due to its importance, it has been a fundamental tool for various areas. One of the applications of AI can be seen in the health domain, particularly in pharmacy, various efforts have been made to solve tasks in an automated way in the pharmaceutical area, which range from the distribution of drugs, the interaction from chatbots with patients and follow-up medical control, to support to find a diagnosis. This article describes relevant research in the area, providing an overview of the importance of AI in pharmacy.